The Relevance of Time in International Law (Polish Yearbook of International Law, 2023)
Law is grounded in time and is constantly shaped by historical circumstances. Treaties, produced by voluntary acts at a given point in time, remain generally in force without a formal endpoint, while customary law arises from practice and lacks specifc points of departure and conclusion. Through the practice of their application, both treaties and customary law may change their content and meaning to a far greater extent than domestic rules. Generally, international law resists retroactive application. However the recognition of sovereign equality to all States in the process of decolonization represents an example of profound change. While the problems deriving from armed conﬂict and former colonial domination must be assessed by the standards of their epoch and not by having recourse to the rules and principles of our time, at the same time it must be borne in mind that many of the acts considered perfectly lawful when they occurred were marred by deep injustices, producing eﬀects which need to be addressed by the law of our time.